Judicial Interpretation: the Impact on Individual and Society in Malaysia - Balasingam, Usharani (International Journal of Engineering and Technology, 2018)
Malaysia is a multiracial country that prides itself in its interracial and interreligious mix and its peaceful and tolerant co-existence among its citizens. Family units are deemed sacrosanct and the base upon which a society and a nation resides. In any breakdown of a marriage, the unit undergoes untold suffering and misery. The pain is even more excruciating when the status quo of the religion of the child of the civil marriage is then abruptly disrupted by the unilateral action of the converted spouse which impedes on the rights and lives of the unconverted spouse and child. The situation in Malaysia is that it is possible given the case of Deepa (2016) for a converted spouse to convert a child of civil marriage unilaterally and also then to file custody for the child in the syariah court to forestall any decision made by the civil courts on custody or recovery orders. The paper intends to demonstrate how judicial interpretation in the case of Deepa has changed the landscape of family law in Malaysia and impacted rights and lives of the affected sections of her people. The case of Deepa has created a change in the civil family law by reading in a jurisdiction of the civil courts over a Muslim child and the creation of a presumption that a child of seven years has the capacity to make an independent judgement on their interest (without the need for additional evidence to collaborate the fact).TheÂ presumption creation is arguably madeÂ in the case of Deepa to family civil law to accommodate the Federal Courtâ€™s decision in reversing the Court of Appeal and High Court decisions on custody orders awarding the custody of both the children of the civil marriage to the non â€“convert mother. This is arguably it is submitted is a result of judicial interpretation driven by a need to justify a decision rather than to reach a decision.Â The case cited in Deepa to argue in support of the presumption will be analysed to consider the extent the creation of this presumption is supported. It is the argument that the judicial interpretation in Deepa case is one driven to support a given outcome for the change in the award of custody and the creation of the presumption is the means by which this is achieved. It does not change the fact that however it has become a legal precedent for all civil family cases. It is submitted that the civil courts are unwilling disregard or not give cognisant to unilateral conversion of the child of a civil marriage. This has shaped the direction and/or the judicial interpretation the civil courts have taken over this issue in spite of it being contrary to pronouncements in existing case precedents as will be demonstrated in this paper. The issue of unilateral conversion recognised by the civil courts is an issue that is sensitive and fragile causing tensions, divides and conflicts not only between the affected parties in a domestic civil marriage breakdown case over custody and the religion of an infant who was converted by the converted spouse into the Muslim religion but between the races and civil society. The case of Deepa caused and required the move by the Parliament to amend the law so as to forestall unilateral conversion. However the same has also been shelved at the moment. The paperâ€™s aim is that in conducting statute and case reviews primarily from a family law perspective to evidence arguments in the furtherance for the move made by the cabinet to be revived.Â